Compensation-signal-driven control for a class of nonlinear uncertain systems. (March 2021) - Zhao, Zhi-Liang; Chai, Tianyou; Wei, Cui; Liu, Dongxu; Liu, Tengfei; Jiang, Zhong-Ping
Abstract: This paper proposes a novel compensation-signal-driven control design method for a class of continuous-time nonlinear uncertain systems. It provides a systematic convergence and stability result on the discrete-time compensation control for continuous-time nonlinear uncertain systems. The key idea is to compensate the uncertainty at the current sampling instant by using a true value of the uncertainty at the last sampling instant. A rigorous convergence and stability result on the discrete-time compensation control is obtained by developing an eigenvalues-and-sequences-based analytic method. It is shown that the tracking error can be made arbitrarily small if the sampling period is sufficiently small. When the system functions are time-independent, the tracking error converges to zero as time tends to infinity. A robotic manipulator model is used in simulations to validate the efficacy of the proposed method.